2016
DOI: 10.1186/s12929-015-0217-0
|View full text |Cite
|
Sign up to set email alerts
|

Renin gene rs1464816 polymorphism contributes to chronic kidney disease progression in ADPKD

Abstract: Background: Autosomal dominant polycystic kidney disease (ADPKD) is a monogenic disorder and is a common genetic cause of chronic renal failure in children and adults. The enzyme renin plays a key role in the RAAS cascade and an important role in the development of hypertension and progression of renal disease in ADPKD. The present study is aimed to investigate the potential modifier effect of REN gene polymorphisms on the progression of chronic kidney disease (CKD) in ADPKD. Methods: We analyzed 102 ADPKD pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 38 publications
0
61
0
Order By: Relevance
“…Previous studies have shown that mitochondrial ROS induce the activation of a large number of mitochondrial apoptotic proteins, leading to cellular apoptosis and organ damage. The functions of two particularly important organs, the liver and the brain, decline gradually due to the attack of ROS during the ageing process 36 . First, the liver has a vitally important function of detoxification, and D-gal is mainly metabolized in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that mitochondrial ROS induce the activation of a large number of mitochondrial apoptotic proteins, leading to cellular apoptosis and organ damage. The functions of two particularly important organs, the liver and the brain, decline gradually due to the attack of ROS during the ageing process 36 . First, the liver has a vitally important function of detoxification, and D-gal is mainly metabolized in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…We have already observed an induction of Ezrin and CCL5 proteins in HCC1937 cells co-treated with cmCAFs and also in MAF. ERM protein complex when activated, inhibits cell adhesion and enhances migration and invasion 44 . Ezrin is found to be more crucial than Moesin and Radixin for tumor induction 45 and if Ezrin is inhibited, Radixin and Moesin will also be inhibited 46 .…”
Section: Discussionmentioning
confidence: 99%
“…In a recent report, mice permanently reconstituted with a human immune system and subsequently intraperitoneally injected with HIV-1 were able to reflect the course of viral infection as reported in humans and recapitulate similar HIV-associated neuropathological disorders. Specifically, these mice exhibited CD8 + T-cell depletion, development of meningitis and as infection progressed, entry of monocytes into the brain also accelerated [ 75 ]; phenomenons all which have been reported in HIV-patients [ 76 78 ]. Follow-up work by the same group report in HIV-1-positive humanized mice (infected with HIV at birth), as the infection progressed, neuronal integrity lessened, thereby revealing a correlation between continual viral replication and neuronal dysfunction [ 79 ].…”
Section: Discussionmentioning
confidence: 99%